2011
DOI: 10.1080/09687599.2011.618740
|View full text |Cite
|
Sign up to set email alerts
|

En/countering disablement in school life in Australia: children talk about peer relations and living with illness and disability

Abstract: This paper reports the experiential accounts of 24 young people with physical disability or chronic illness as they make the transition to junior high school, with a particular focus on their social experiences with peers and friends. Children's reports were examined in a reflexive, disability studies framework, in which commonalities and difference in experience were examined. These reports highlight a common experience of disability-related harassment and differential experiences of friendship, peer rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…While this behaviour was consistent with the literature, where sport can empower disabled individuals to actively resist and challenge these ableist discourses (McMaugh 2011), and hold simultaneous beliefs (Slater et al 2012), the findings revealed how ego-and task-oriented goals may coexist within the incremental beliefs of para-athletes, given that there was no clear evidence para-athletes endorsed dominant entity beliefs outside of sport. Thus, through investigating the nuanced motivational processes and sequences which led to the dominant incremental beliefs of para-athletes (Vella et al 2016), it is possible that behaviours associated with entity beliefs (i.e., accepting fixed conditions which led to improved abilities) may not be detrimental in all circumstances as implied by the past studies (e.g., Jowett and Spray 2013), and presents a fruitful line of inquiry to be explored further.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While this behaviour was consistent with the literature, where sport can empower disabled individuals to actively resist and challenge these ableist discourses (McMaugh 2011), and hold simultaneous beliefs (Slater et al 2012), the findings revealed how ego-and task-oriented goals may coexist within the incremental beliefs of para-athletes, given that there was no clear evidence para-athletes endorsed dominant entity beliefs outside of sport. Thus, through investigating the nuanced motivational processes and sequences which led to the dominant incremental beliefs of para-athletes (Vella et al 2016), it is possible that behaviours associated with entity beliefs (i.e., accepting fixed conditions which led to improved abilities) may not be detrimental in all circumstances as implied by the past studies (e.g., Jowett and Spray 2013), and presents a fruitful line of inquiry to be explored further.…”
Section: Resultssupporting
confidence: 86%
“…Enforcing the notion that participants are active agents capable of resisting the prevailing stereotypes surrounding disability and challenging the dominant 'able-bodied gaze' which defined disabled individuals as 'the other' (Le Clair 2011, McMaugh 2011, the aforementioned extracts emphasise how imperative it is to understand that disability does not mean inability. As illustrated by P3, her cane may be an extension of her senses but it should not be perceived as a 'declaration' of her limitations.…”
Section: The 'Disability' Labelmentioning
confidence: 99%
“…This research shows that students are not just victims of ableist discourses that mark them as abnormal and facilitate their exclusion from participating in (physical) activities with peers. As Doubt and McCall (2003) and McMaugh (2011) argue, disabled students also resist these oppressive How physically disabled construct and position their body 155 structures, produce alternative discourses and perform strategies to manage and/or minimize their marginalization.…”
Section: Ableism In Sport and Schoolmentioning
confidence: 96%
“…For example, some children with disability experience exclusion (McMaugh, 2011); access to inclusive education is unreliable (QPPD, 2011), or is denied (Anderson & Boyle, 2015). According to Boyle and Sharma (2015), many countries continue to categorise and separate children with disability from typical educational experiences.…”
Section: Current Understandings Of the School Lives Of Children Withmentioning
confidence: 99%
“…She eagerly agreed to participate. Although parents' stories about schooling are inevitably entwined with the stories of their children, and the contribution of the child's voice to academic research is increasingly recognised (McMaugh, 2011), the focus of my research was parental decision-making so it was Nelly's, rather than Josh's, point of view that I was keen to capture. Now, as I sit across from her, my mind goes back over Nelly's story and arrives at the remarkable place she is now.…”
Section: Introductionmentioning
confidence: 99%